Research Progress on Durability of Cellulose Fiber-Reinforced Cement-Based Composites - Jie Liu; Chun Lv (International Journal of Polymer Science)
The performance of cellulose fiber-reinforced cement-based composites (CFCCs) depends not only on the characteristics of the cement matrix and fibers but also on the bonding property of the matrix and fibers. The durability of cement-based composites including various properties such as impermeability, frost resistance, and carbonization resistance has an important impact on the long-term service life of the matrix structure. The presence of a large number of hydroxyl groups on the molecular chain of cellulose can promote the formation of intra- and intermolecular hydrogen bonds of cellulose. This special structure imparts the cellulose high hydrophilicity, which leads the cement hydration C-S-H gel to adhere to the surface of cellulosic fibers (CFs) and induce its growth. The cavity of CFs has good water absorption and can be used as an internal curing fiber for the continuous hydration of cement-based composites. But CFs in the Portland cement matrix tend to deteriorate under strong alkali conditions. This paper presents a review of the research on the durability of CFCCs. The methods and paths to improve the durability of CFCCs are summarized and analyzed from the perspectives of the internal curing of CFs, the deterioration of the performance of CFs in the matrix, and the use of many types of supplementary cementitious materials. Finally, the development and engineering application of CFCCs have been prospected.